Oxygen Concentration Plays a Critical Role in Fibrinogen-Mediated Platelet Activation via Inactivation of αIIbβ3 and Modulation of Fibrinogen - Sophie V. L. Leonard; Zoe Booth; Leigh Naylor-Adamson; Lewis Bibby; Katie S. Wraith; Giordano Pula; Monica Arman; Simon D. J. Calaminus (Biomolecules)
In the vascular system, pathological conditions that cause hypoxia are associated with increased platelet activity and thrombosis. Using a platelet spreading assay, we show that severe hypoxia (i.e., 1%), venous (i.e., 5%), and, surprisingly, arterial (i.e., 12%) oxygen concentrations cause a significant reduction in platelet surface area coverage on fibrinogen in comparison to atmospheric oxygen condition (i.e., 21% oxygen), whilst adhesion and spreading on collagen and CRP were not affected. Importantly, the addition of thrombin or zinc restored full platelet spreading on fibrinogen, indicating that the inhibition of platelet spreading on fibrinogen was due to defective integrin activation. Analysis of integrin activation with FACs via PAC-1 staining supported a significant reduction in integrin activation in hypoxic conditions. Interestingly, a fibrinogen matrix prepared at 1%, 5%, or 12% oxygen failed to induce full platelet spreading, even when the experiments were performed at atmospheric oxygen concentration, indicating that the structure and activity of the fibrinogen coating is affected by oxygen. The effect of oxygen on different matrix proteins is critical to understand, as these data clearly demonstrate that collagen and CRP can support platelet activation at all O2 concentrations, whilst fibrinogen mediated platelet activation and spreading is lost at physiological and pathological O2 concentrations. These data have clear implications for thrombus formation data and highlight the role of oxygen in regulating platelet function.